Consultation on kidney stones, Copenhagen 2019: aspects of intracorporeal lithotripsy in flexible ureterorenoscopy - Lildal, Søren Kissow (World J Urol, 2020)
PURPOSE: To summarize current knowledge on intracorporeal laser lithotripsy in flexible ureterorenoscopy (fURS), regarding basics of laser lithotripsy, technical aspects, stone clearance, lithotripsy strategies, laser technologies, endoscopes, and safety. METHODS: A scoping review approach was applied to search literature in PubMed, EMBASE, and Web of Science. Consensus was reached through discussions at the Consultation on Kidney Stones held in September 2019 in Copenhagen, Denmark. RESULTS AND CONCLUSIONS: Lasers are widely used for lithotripsy during fURS. The Holmium laser is still the predominant technology, and specific settings for dusting and fragmenting have evolved, which has expanded the role of fURS in stone management. Pulse modulation can increase stone ablation efficacy, possibly by minimizing stone retropulsion. Thulium fibre laser was recently introduced, and this technology may improve laser lithotripsy efficiency. Small fibres give better irrigation, accessibility, and efficiency. To achieve optimal results, laser settings should be adjusted for the individual stone. There is no consensus whether the fragmentation and basketing strategy is preferable to the dusting strategy for increasing stone-free rate. On the contrary, different stone scenarios call for different lithotripsy approaches. Furthermore, for large stone burdens, all laser settings and lithotripsy strategies must be applied to achieve optimal results. Technology for removing dust from the kidney should be in focus in future research and development. Safety concerns about fURS laser lithotripsy include high intrarenal pressures and temperatures, and measures to reduce both those aspects must be taken to avoid complications. Technology to control these parameters should be targeted in further studies.